NVQ engineering level 2 mechanical units - Salmon, David (Longman NVQ, 1998)
This workbook provides a programme of work for the development of the practical skills and knowledge required for the three mechanical option units of the NVQ Engineering Manufacture (Foundation) at Level 2. It is designed for use in the college, the training organisation or the workplace and is part of a series of workbooks covering the complete NVQ scheme. The book is an invaluable resource for both trainee and training provider. Trainees will acquire the necessary underpinning knowledge by using this book and will be able to demonstrate the practical skill required for assessment by completing the set practical tasks and exercises. There are over 24 practical and progressive exercises and activities which assist the trainee in demonstrating their competence in each NVQ element. The book also discusses safe working practices.